On the genus Gonioctena Chevrolat (Coleoptera: Chrysomelidae: Chrysomelinae), with descriptions of seven new species from the Oriental region and Palaearctic China - Cho, Hee-Wook; Borowiec, Lech (Zootaxa, 2016)
Seven new species of Gonioctena Chevrolat are described from the Oriental region and Palaearctic China: Gonioctena (Asiphytodecta) mausonensis sp. nov., G. (A.) oudai sp. nov., G. (Brachyphytodecta) arunensis sp. nov., G. (B.) mauroi sp. nov., G. (B.) medvedevi sp. nov., G. (Gonioctena) fujiana sp. nov. and G. (G.) mongolica sp. nov. Gonioctena (Asiphytodecta) subgeminata tonkinensis (Chen, 1934) is removed from synonymy with G. (A.) subgeminata (Chen, 1934) and raised to the species level. Gonioctena (Gonioctena) suwai Takizawa, 1985 is synonymized with G. (G.) ogloblini Medvedev & Dubeshko, 1972. Gonioctena (Asiphytodecta) sapaensis nom. nov. is proposed as a replacement name for G. (A.) unicolor Medvedev, 1987 not Phytodecta quinquepunctata var. unicolor Weise, 1884. Lectotype is designated for Phytodecta subgeminatus var. tonkinensis Chen, 1934.